2006
DOI: 10.1021/jp055036y
|View full text |Cite
|
Sign up to set email alerts
|

Toward Understanding the Hofmeister Series. 3. Effects of Sodium Halides on the Molecular Organization of H2O As Probed by 1-Propanol

Abstract: We investigated the effects of NaF, NaCl, NaBr, and NaI on the molecular organization of H2O by a calorimetric methodology developed by us earlier. We use the third derivative quantities of G pertaining to 1-propanol (1P) in ternary 1P-a salt-H2O as a probe to elucidate the effects of a salt on H2O. We found that NaF and NaCl worked as hydration centers. The hydration numbers were 19 +/- 2 for NaF and 7.5 +/- 0.6 for NaCl. Furthermore, the bulk H2O away from the hydration shell was found unaffected by the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
63
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 41 publications
11
63
1
Order By: Relevance
“…A further aspect to consider is the issue of solvation of free anions in solution. The Hofmeister series or bias confirms [53,54] the low relative hydration of ClO 4 À compared to other anions in this study and is consistent therefore with the lack of exchange observed for [Ag(4,4'-bipy)ClO 4 ] 1 in water.…”
Section: Resultssupporting
confidence: 89%
“…A further aspect to consider is the issue of solvation of free anions in solution. The Hofmeister series or bias confirms [53,54] the low relative hydration of ClO 4 À compared to other anions in this study and is consistent therefore with the lack of exchange observed for [Ag(4,4'-bipy)ClO 4 ] 1 in water.…”
Section: Resultssupporting
confidence: 89%
“…Recent works concerning the effect of salts on the aqueous solubility of complex molecules 37,[43][44][45][46] are suggesting that watermediated interactions between hydrophobic solutes and salt ions are closely related to the extent of hydration of individual ions.…”
Section: Discussionmentioning
confidence: 99%
“…These authors concluded that ions with higher polarizability and ionic radii reside near the surface of water clusters, whereas smaller size and polarizability ions remained fully solvated at the interior of the cluster. The effects of halide ions on the structure of water have been also studied experimentally [27]. It was found that chloride presents a cosmotropic effect on the structure of water, whereas bromide shows a chaotropic behavior.…”
Section: Discussionmentioning
confidence: 99%